Climate Services in Senegal: Media training and field trip report - Meadu, Vanessa; Zougmoré, Robert B.; Touré, Sékou F. (2015)
To demonstrate the success of the Senegal-based project on strengthening the scaling up of climate services, and enhance capacity for regional media to report effectively on climate change issues, CCAFS carried out media training and site visit from 28 to 30 September 2015. This activity was co-led by the CCAFS West Africa team and Coordinating Unit, in collaboration with local partners, and media experts. This report summarized key activities, outputs and outcomes from the visit. Both activities were designed to take advantage of the keen interest reporters are paying to climate change this year to focus their attention on agriculture’s role as a climate solution, especially through ground experiences and successes of CCAFS-led activities in Senegal (climate information services, climate-smart villages, etc.).